Clinical device-related article surface characterization of explanted endovascular stents : evidence of in vivo corrosion - Halwani, Dina O.; Anderson, Peter G.; Anayiotos, Andreas (My University, 2010)
Limited information exists regarding the in vivo stability of endovascular stents. Nine excised human vascular segments with implanted stents (n = 16) manufactured from stainless steel, nickel-titanium, tantalum, and cobalt-based alloys were analyzed. The stent/tissue components were separated using an established tissue dissolution protocol and control and explanted stents were evaluated by digital optical and electron microscopy. Metallic content in surrounding tissues was measured by mass spectroscopy. Surface alterations, consistent with corrosion mediated by electrochemical and mechanical factors, were observed in 9 of the 16 explanted stents and were absent from control stents. Tissue dissolved from around corroded stents corresponded with a higher metallic content. The effect of these changes in the microtopography of stents on their mechanical properties (fatigue strength and fracture limit) in addition to the potential for released metallic debris contributing to the biological mechanisms of in-stent restenosis supports the need for further investigations.
Keywords: Fretting corrosion; Biomechanics; Tantalum; Titanium; Open access publishing